Coagulation in chronic liver disease and the use of prothrombin complex concentrate for an emergent procedure: a case report and review of literature - Matthew Laubham; Eric Kallwitz (Greater Baltimore Medical Center, 2018)
Synthetic dysfunction observed in cirrhosis results in altered production of procoagulants and anticoagulants that can lead to both bleeding and thrombotic events, respectively. In patients with decompensated cirrhosis, frequent hospital visits often require bedside procedures such as diagnostic paracenteses, thoracenteses and endoscopy. It can be difficult to determine at what coagulation threshold procedures can safely be performed. Currently, the most common therapies given pre-procedurally include fresh frozen plasma (FFP) and vitamin K. The effectiveness of these treatments is estimated by international normalized ratio (INR), an imprecise measure of coagulation in the setting of cirrhosis. Transfusion with FFP may lead to detrimental side effects, including worsening volume overload and increased portal hypertension. We present a case of a 60-year-old patient intubated for acute hypoxic respiratory failure secondary to volume overload who subsequently developed bilateral pneumothoraces, requiring immediate chest tube placement. In this case, the patient had ongoing hepatic decompensation with volume overload and acute worsening of coagulopathy with an INR of 4.2. In this setting, 4-Factor Prothrombin Complex Concentrate (4F-PCC) was chosen to correct coagulation parameters with a low infusion volume. One hour following administration, INR was 1.5. Chest tubes were placed bilaterally and oxygenation improved without bleeding complications. While the data is still lacking, 4F-PCC may be considered for urgent and emergency situations in cirrhotic patients.